Variation in body size and metamorphic traits of Iberian spadefoot toads over a short geographic distance - Marangoni, Federico (2008)
Determinants of geographic variation in body size are often poorly understood, especially in organisms with complex life cycles. We examined patterns of adult body size and metamorphic traits variation in Iberian spadefoot toad (Pelobates cultripes) populations, which exhibit an extreme reduction in adult body size, 71.6% reduction in body mass, within just about 30 km at south-western Spain. We hypothesized that size at and time to metamorphosis would be predictive of the spatial pattern observed in adult body size. Larvae from eight populations were raised in a common garden experiment at two different larval densities that allow to differentiate whether population divergence was genetically based or was simply a reflection of environmental variation and, in addition, whether this population divergence was modulated by differing crowding larval environments. Larger adult size populations had higher larval growth rates, attaining larger sizes at metamorphosis, and exhibited higher survival than smaller-sized populations at both densities, although accentuated at a low larval density. These population differences appeared to be consistent once embryo size variation was controlled for, suggesting that this phenotypic divergence is not due to maternal effects. Our results suggest considerable genetic differentiation in metamorphic traits that parallels and may be a causal determinant of geographic variation in adult body size. © 2008 The Authors.